Hong Kong Special Administrative Region : Macroeconomic Impact of an Aging Population in a Highly Open Economy - Leigh, Lamin (Washington, D.C. : International Monetary Fund, 2006)
Hong Kong SAR's population is aging rapidly. This paper concludes that, without a change in policies, aging could adversely affect growth and living standards. While higher labor productivity growth and increased migration of younger skilled workers from the Chinese mainland, would attenuate the economic impact of aging, they would not offset it fully. Aging will also put pressure on public finances, particularly as a result of rising health care costs. There is a relatively narrow window of opportunity to implement policies to lessen the impact of aging, given that the demographic effects could start setting in as early as 2015 when the working population's support ratio peaks. In recent years, the Hong Kong SAR authorities have been focusing on policies that could help limit the fiscal impact of aging, including continued expenditure restraint on non-age-sensitive areas, reform of health care financing (including introducing private health insurance system), and tax reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet